The effects of instability and additional hand support on anticipatory postural adjustments in leg, trunk, and arm muscles during standing - Slijper, Harm; Latash, Mark (Experimental brain research, 2000)
We investigated the role of additional perceptual information (finger touch) and additional mechanical support (hand grasp) on the anticipatory postural adjustments (APAs) associated with fast arm movements performed by standing subjects. The subjects performed fast, unilateral shoulder ante-flexion movements while standing on a stable force platform or on an unstable board with instability in a sagittal or in a frontal plane. Changes in the background activity of leg, trunk, and arm muscles and displacements of the center of pressure were quantified within time intervals typical for APAs. Leg and trunk muscles showed a significant drop in APAs with added finger touch and no further changes when the touch was substituted with hand grasp. Arm muscles showed no changes or a small drop in APAs with touch and a significant increase in APAs with grasp. These changes were seen during both stable and unstable standing. We conclude that APAs can show changes associated not only with mechanical aspects of a task, but also with its perceptual aspects. Based on the equilibrium-point hypothesis of motor control, an additional analysis of APAs was performed. With additional support, we observed a significant modulation of an index related to the co-activation of agonist-antagonist muscle pairs, while no changes in reciprocal activation were found. A similar analysis performed across all the leg and trunk muscles with respect to control of the center of mass lead to similar results. We conclude that the central nervous system seems to simplify adjustments of control patterns to changes in task parameters by modulation of only one of the two major central commands.